Maintenance management of beach house resort in coastal area / Noor Asyikin Mohd Naru - Mohd Naru, Noor Asyikin (Faculty of Architecture,Planning and Surveying, 2015)
The Maintenance Management have their own guidelines based on the types of building which is commercial building, residential buildings, institutions buildings, etc to maintain their building. Every resort building need a maintenance works so that the building should have their own maintenance management to keep maintain the condition of building. The beach house resort in coastal area need the maintenance management for keep maintain that building as a tourism places. The resort building also should be considered when the designers specify the building materials to keep maintain the building in long term. Maintenance management of the resort in coastal area are very important because of the highest humidity problem. It will give the more of impact to that adjacent building whether the houses or resort. Because of that, the adjacent building have many problem such as corrosion, lack of the building's colour, etc. but the management of the resort building should be provide a comfortable place to the tourist or any visitor to the resort. Every resort should have maintenance management for keep maintain and control the humidity problems due of wind and weather. When the building have their own maintenance management,they can be perform daily housekeeping and cleaning to maintain a properly presentable facility, promptly respond and repair minor discrepancies in the facility,develop and execute a system of regularly scheduled maintenance actions to prevent premature failure of the facility and its system and components, complete major repairs based on lowest life-cycle cost, operate the facility utilities in the most economical manner while providing necessary reliability, and etc. The environment in coastal area is the different working environment in maintenance so that the owner of resort need occupational health and safety management systems to prevent and minimize the accident to the tourist or visitor. The resort building in coastal area have a different practice, the maintenance programme should comprised of three basic components organization, inspection, and maintenance plan. The management of resort must provide guidance to the resort in preparing detailed list of areas, spaces, materials, furniture, and equipment to be maintained as well as a list of defect to be corrected. The users satisfaction also important to the future life of the building.